Alguns significados para mães de filhos com síndrome de Down - Freitas, Denise Esper de (2008)
How to Know and analyze the meaning of motherhood for mothers of children with Down Syndrome, was the original question of this research. From this enquiry about the perception of these mothers, the research focused on the understanding, trying to check what the challenges faced and how they deal with the situation after the birth of a child with Down Syndrome. Ten questions were asked for mothers of individuals with Down syndrome from APAE of the city of Jaguariúna, Brazil, investigated during the second half of 2007 and first half of 2008. The sample was stratified by age, 05 women with less than 35 years and 05 women over 35 years of age. After, 2 mothers were selected, by deliberate choice, of the 10 that started the program, being one of them illiterate and another with a higher level. It was made a semi-open interview with them, seeking to know the motivations of motherhood, the knowledge of the risk involved and the meaning of having a child with Down Syndrome, finally, to obtain data from first day of the pregnancy until the present day. The results of questions held to the 10 mothers were aware of the risks of gestational and concern about the possibility of the child born disabled, but low number of planned pregnancies, high emotional impact of the diagnosis at birth for most mothers, almost all relate heavy load Working in the care of disabled child; professional support involved, but uncoordinated actions of health in both the public and the private sector; few mothers said that the choice of motherhood was due to take place as a women but almost all women ,however, said that they feel satisfied with motherhood even a disabled child. About the 2 mothers with drastic financial gap and education, to realize that despite all the difficulties of illiterate mother seems to be a better acceptance and adaptation of the child deficient in both subjective afield as the family and social environment in which they live. Is clear to see, in relation to the mother of the best social level a bigger suffering to live with the disabled child, observation corroborated by other similar searches in our area. Finally our results also agree with the view according to with what is today called the maternal instinct, is a feeling more prone to social aspects, psychological and cultural, than the biological determinants.